PEMBENTUKAN KARAKTER SOCIAL AWARENESS MELALUI PENDIDIKAN AGAMA ISLAM BERBASIS HABBIT FORMING - Siti Hikmatul Aisyah; Ulil Hidayah (LPPM STAI Muhammadiyah Probolinggo, 2024)
Social awareness or Kesadaran sosial in Bahasa Indonesia is a personality trait of individuals who possess intelligence and sensitivity towards the social environment in accordance with religious and social norms. The development of social awareness needs to be cultivated and ingrained through the educational process. Therefore, this research focuses on the study of habit-forming practices carried out at Mts. Zainul Irsyad Probolinggo through Islamic religious education integrated with the students' environment. By employing the analytical tools of Thomas Lickona and Ivan Pavlov's theories, it was found that character education is an effort to shape an individual's understanding of ethical values deliberately. However, according to Pavlov, instilling character education in an individual requires repetitive stimuli, thus referring to it as habituation. The results of this research indicate that the habit-forming practices of Islamic religious education at Madrasah Tsanawiyah have an impact on the social awareness of students at Madrasah Tsanawiyah Zainul Irsyad Probolinggo, manifested in their social and moral skills within the community environment.